Determination of Traction Separation Law for Interfacial Failure in Adhesive Joints at Different Loading Rates. Issue 10 (2nd October 2016) - Desai, Chaitanya K.; Basu, Sumit; Parameswaran, Venkitanarayanan
Abstract : Cohesive zone modeling (CZM) has been extensively used in recent years to simulate failure in adhesive joints. Accurate determination of the traction–separation law (TSL) (or parameters of the CZM) is very crucial to the success of this approach. Recent experimental investigations have indicated that loading rate influences the TSL/CZM parameters. In this work we have attempted to measure the TSL using two different approaches for an adherend/adhesive system which always fails by interfacial failure. In the first approach, the TSL is obtained by differentiating the experimentally measured J integral by the opening displacement. The second, an inverse approach, involves a finite element (FE) analysis in which the adhesive layer is also modeled and cohesive elements are used to model the interfacial failure. The TSL is then obtained iteratively by matching the numerical load–displacement data to that obtained in experiments. We show that the first approach yielded TSLs which are dependent on both adhesive layer thickness and the loading rate, whereas the second approach yielded a TSL which is independent of the adhesive layer thickness and the loading rate. Therefore, the TSL obtained from the second approach is intrinsic to the adhesive/adherend pair and in that sense is unique.